2003
DOI: 10.1364/ol.28.001680
|View full text |Cite
|
Sign up to set email alerts
|

X-ray laser beam with diffraction-limited divergence generated with two gain media

Abstract: We demonstrate an x-ray laser at a wavelength of 13.9 nm with a beam divergence of 0.2 mrad, which is 1.8 times the diffraction limit. The x-ray laser is generated with two gain media; the seed x-ray pulse from the first medium is amplified in the second medium. The effect of refraction on x-ray propagation is reduced by spatially and temporally controlling the injection of the seed x-ray to the second medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…The laser pulses are focused with a line shape of 6.5 mm 20 μm on flat silver targets with an irradiance of the heating pulse of ~10 15 W/cm 2 . Two targets separated for 20 cm were used to improve the energy and the beam divergence of the x-ray laser; a part of the x-ray laser generated in the first medium is used as the seed x-ray laser, and it is injected into the successive second medium, which is used as an amplifier with calm density gradient [6]. The typical output energy of the x-ray laser emission was 0.5 μJ, and the beam divergence was obtained to be 0.5 2 mrad.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser pulses are focused with a line shape of 6.5 mm 20 μm on flat silver targets with an irradiance of the heating pulse of ~10 15 W/cm 2 . Two targets separated for 20 cm were used to improve the energy and the beam divergence of the x-ray laser; a part of the x-ray laser generated in the first medium is used as the seed x-ray laser, and it is injected into the successive second medium, which is used as an amplifier with calm density gradient [6]. The typical output energy of the x-ray laser emission was 0.5 μJ, and the beam divergence was obtained to be 0.5 2 mrad.…”
Section: Methodsmentioning
confidence: 99%
“…The transient collisional excitation (TCE) x-ray lasers have been intensively studied, because they can achieve a high gain of a few tens per centimeter [3,4] and picosecond pulse duration [5] using a tabletop laser system. The large beam divergence up to 10 mrad, which had been a weak point of the TCE x-ray laser, was dramatically improved to be less than 0.5 mrad using two gain media with oscillator-amplifier configuration [6,7]. On the other hand, optical technologies around 13.5 nm have been receiving strong interest for next-generation lithography applications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The two gain medium plasmas of the EUV laser were generated by irradiating flat silver targets with two laser pulses with 1053 nm wavelength. The two pulses were separated by 2 ns, each having prepulse duration of 200 ps and main pulse duration of 3ps [6]. The pulse energy of the EUV laser pulse was typically 0.5 mJ and the duration was 7 ps.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, on the assertion whether there is a theoretical stable state for the simultaneous existence of negative refractive index (NRI) and net gain, physicists still have opposite opinions [14][15][16][17][18][19] . In optics, a diverse family of 'gain media', primarily based on doped crystalline, semiconductors, dyes and gases, have been widely used in laser technologies [20][21][22][23][24] . Simulations have shown that by placing optical gain media (that is, optically pumped laser dyes) in fishnet metamaterial cells, the resulting optical 'gain metamaterial' is able to exhibit an NRI in a narrow bandwidth without violating causality 4,7 .…”
mentioning
confidence: 99%